2014
DOI: 10.1007/978-3-319-00203-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Generalisation in Practice Within National Mapping Agencies

Abstract: National Mapping Agencies (NMAs) are still among the main end users of research into automated generalisation, which is transferred into their production lines via various means. This chapter includes contributions from seven NMAs, illustrating how automated generalisation is used in practice within their partly or fully automated databases and maps production lines, what results are currently being obtained and what further developments are on-going or planned. A contribution by the European Joint Research Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…However, only recently NMAs succeeded to implement automated generalisation to derive a complete map with no or little human interaction (Duchêne et al 2014). These achievements have several reasons First, successful research results have found their way into software.…”
Section: Developments Within Nmasmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only recently NMAs succeeded to implement automated generalisation to derive a complete map with no or little human interaction (Duchêne et al 2014). These achievements have several reasons First, successful research results have found their way into software.…”
Section: Developments Within Nmasmentioning
confidence: 99%
“…This variation is explained by the history and culture within an NMA (Duchêne et al 2014). Some NMAs have a vivid and lengthy history in studying automation of mapping procedures, which has also contributed to the current implementation of algorithms in commercial software.…”
Section: Approaches For Generalisationmentioning
confidence: 99%
“…978-1-4503-3131-9/14/11 ...$15.00 http://dx.doi.org/10.1145/2666310.2666414. mapping agencies typically produce at a small number of different scales [5]. For interactive maps that allow for continuous zooming, however, many problems of automatic generalization are still open.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in data collection and computer processing speeds have improved the volume and variety of data sources, and issues related to full automation of generalization and data modeling have become a higher priority among researchers in the US and abroad (Mackaness, Raus, & Sarjakoski, ; Burghardt, Duchêne, Mackaness, ). The need to automate data processing for multi‐scale data production is articulated clearly by several federal agencies (Foerster, Stoter, & Kraak, ; Duchêne et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The US Geological Survey (USGS) and other national mapping agencies are researching methods to generalize cartographic data in an automated fashion. Several researchers and agencies have developed algorithms and workflows to accomplish this task, with varying levels of success (Duchêne et al, ). The National Hydrography Dataset (NHD), which is maintained and distributed by the USGS, is a comprehensive vector dataset of features representing surface water features in the US (USGS, ).…”
Section: Introductionmentioning
confidence: 99%